Conversations with contemporary cinematographers : the eye behind the lens - Frost, Jacqueline B., 1957- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Packed with gems of wisdom from the current 'masters of light', this collection of conversations with twenty leading contemporary cinematographers provides invaluable insight into the art and craft of cinematography. Jacqueline Frost's interviews provide unprecedented insight into the role as cinematographers discuss selecting projects, the conceptual and creative thinking that goes into devising a visual strategy, working with the script, collaborating with leading directors such as Martin Scorcese, Spike Lee, and Ava DuVernay, the impact of changing technology, and offer advice for aspiring cinematographers. Interviews include Maryse Alberti, John Bailey, Robert Elswit, Kirsten Johnson, Kira Kelly, Ellen Kuras, Edward Lachman, Matthew Libatique, John Lindley, Seamus McGarvey, Reed Morano, Polly Morgan, Rachel Morrison, Rodrigo Prieto, Cynthia Pusheck, Harris Savides, Nancy Schrieber, John Seale, Sandi Sissel, Dante Spinotti, Salvatore Totino, Amy Vincent, and Mandy Walker. Filled with valuable information and advice for aspiring cinematographers, directors and filmmakers, this is essential reading for anyone interested in the art and craft of cinematography"--
Maryse Alberti, ASC (Collateral beauty, Creed, The wrestler) -- John Bailey, ASC (Ordinary people, In the line of fire, The greatest) -- Robert Elswit, ASC (There will be blood, The Bourne legacy, Salt) -- Kirsten Johnson (Fahrenheit 9/11, Cameraperson, Trapped) -- Kira Kelly (Queen sugar, 13th, Self made) -- Ellen Kuras, ASC (Eternal sunshine of the spotless mind, Blow, Bamboozled) -- Edward Lachman, ASC (Dark waters, Carol, Erin Brockovich) -- Matthew Libatique, ASC (A star is born, Black Swan, Venom) -- John Lindley, ASC (Reservation Road, You've got mail, Pleasantville) -- Seamus McGarvey, ASC, BSC (The greatest showman, Atonement, The hours) -- Reed Morano, ASC (The handmaid's tale, I think we're alone now, The godmother) -- Polly Morgan, ASC, BSC (A quiet place II, Lucy in the sky, Legion) -- Rachel Morrison, ASC (Mudbound, Black Panther, Seberg) -- Rodrigo Prieto, ASC, AMC (The Irishman, Brokeback Mountain, Wolf of Wall Street) -- Cynthia Pusheck, ASC (CSI Miami, Good girls revolt, Brother and sisters) -- Harris Savides, ASC (Zodiac, American gangster, Milk) -- Nancy Schrieber, ASC (Mapplethorpe, Motherhood, The Nines) -- John Seale, ASC, ACS (The tourist, The English patient, City of angels) -- Sandi Sissel, ASC, ACS (Salaam Bombay, Mother Teresa, Master and commander) -- Dante Spinotti, ASC, AIC (Public enemies, Red Dragon, Wonder boys) -- Salvatore Totino, ASC, AIC (Everest, The Davinchi Code, Frost/Nixon) -- Amy Vincent, ASC (Footloose, Eves Bayou, Hustle and flow) -- Mandy Walker, ACS, ACS (Australia, Hidden figures, Mulan).
"A Focal Press Book" -- taken from front cover.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Cinematographers -- Interviews; Cinematography; PERFORMING ARTS / Film & Video / General; PERFORMING ARTS / Film & Video / Screenwriting